Comparative pharmacological and histochemical evidence for purinergic inhibitory innervation of the portal vein of the rabbit, but not guinea-pig - Burnstock, Geoffrey (1979)
1 Intramural nerve stimulation elicited a powerful relaxation of the longitudinal muscle of the rabbit portal vein in the presence of atropine and guanethidine, but not of the guinea-pig portal vein. 2 Intramural nerve stimulation of the rabbit portal vein produced a 13 fold increase in release of (3)H-adenyl compounds after preloading with [(3)H]-adenosine. About 50% of this release was abolished by guanethidine. All release was abolished by tetrodotoxin. No significant release of radioactive compounds was observed during intramural nerve stimulation of the guinea-pig portal vein in the presence of guanethidine, although there was a 6 fold increase in release of radioactivity in the absence of drugs. 3 Histochemical studies using quinacrine, which binds ATP showed a fine fluorescent nerve plexus, nerve bundles, and ganglion cells in the rabbit portal vein, but not in the guinea-pig portal vein. This plexus was still present after chemical sympathectomy with 6-hydroxydopamine. 4 Adenosine 5′-triphosphate (ATP) relaxed the rabbit portal vein, but usually produced a biphasic response, consisting of a contraction followed by a relaxation, of the guinea-pig portal vein. 5 Prostaglandins E(1) and E(2) caused contraction of the rabbit portal vein. Indomethacin, a prostaglandin synthesis inhibitor, potentiated the relaxations of the rabbit portal vein produced by both non-adrenergic, non-cholinergic nerve stimulation and ATP. 6 High concentrations of antazoline and phentolamine, which antagonize purinergic responses in the guinea-pig taenia coli, caused a loss of basal tone so that it was not possible to assess their effects on the responses of the portal vein to either non-adrenergic, non-cholinergic nerve stimulation, or ATP. 7 Comparison of the results on the portal vein of the rabbit and guinea-pig provides support for the view that: (i) quinacrine fluorescence can be used to localize purinergic nerves and that the rabbit portal vein is supplied by these nerves; (ii) ATP is released from adrenergic nerve fibres, although, based on histochemical analysis, about 3 to 7 times less than is released from purinergic nerve fibres.